2009
DOI: 10.17221/1075-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Lutein Content in Peas (Pisum sativum L.) in Relation to the Variety, Season and Chlorophyll Content

Abstract: Lutein and β-carotene contents in 32 samples of field peas with green (ii), yellow (I.) and orange cotyledons (orcorc) were determined. The highest lutein concentration ranging between 0.768 and 1.394 mg/100 g was found in varieties with green cotyledons (median 0.978 mg/100 g). Yellow cotyledons contained lower amount of lutein, median = 0.692 mg/100 g. Big variation in lutein content was found in tested breeding lines with orange cotyledons, only 4 lines showed higher lutein content in comparison with the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 6 publications
(5 reference statements)
12
19
1
Order By: Relevance
“…Lutein was the predominant carotenoid in both pea and chickpea. Similar results were observed in previous studies in pea (McCallum et al, 1997;Holasová et al, 2009;Marles et al, 2013), chickpea (Abbo et al, 2005(Abbo et al, , 2010, and wheat (Adom et al, 2003;Hidalgo et al, 2006;Ramachandran et al, 2010). Mean lutein concentration of the pea accessions ranged from 5.6 mg g À1 to 24 mg g À1 which is greater than the previously reported of 7 mg g À1 in yellow cotyledon pea, and 8 mg g À1 to 14 mg g À1 in green cotyledon pea (Holasová et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Lutein was the predominant carotenoid in both pea and chickpea. Similar results were observed in previous studies in pea (McCallum et al, 1997;Holasová et al, 2009;Marles et al, 2013), chickpea (Abbo et al, 2005(Abbo et al, , 2010, and wheat (Adom et al, 2003;Hidalgo et al, 2006;Ramachandran et al, 2010). Mean lutein concentration of the pea accessions ranged from 5.6 mg g À1 to 24 mg g À1 which is greater than the previously reported of 7 mg g À1 in yellow cotyledon pea, and 8 mg g À1 to 14 mg g À1 in green cotyledon pea (Holasová et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…To date, only limited research has been reported related to carotenoids in pea and chickpea seeds using HPLC analysis. Previously, lutein, zeaxanthin and b-cryptoxanthin were reported in chickpea seed (Abbo et al, 2005, Abbo et al, 2010, whereas violaxanthin, lutein, and bcarotene were reported in cotyledons and seed coats of field pea (McCallum et al, 1997;Holasová et al, 2009). Lutein was reported as the major carotenoid in chickpea (Abbo et al, 2005(Abbo et al, , 2010, pea (McCallum et al, 1997;Holasová et al, 2009;Marles et al, 2013) and wheat (Adom et al, 2003;Hidalgo et al, 2006;Ramachandran et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…431 Moreover, Fe uptake by caco-2 cells is inhibited when the phytic 432 acid:Fe molar ratio exceeds 10 (Glahn et al, 2002 (680-1087 mg/100 g) than in the yellow field peas (19-121 mg/ 444 100 g). This is consistent with previous work that shows beta-445 carotene concentrations can vary significantly between green and 446 yellow field peas, with levels in green peas being 10-fold greater 447 (Holasova et al, 2009). Green field pea has higher chlorophyll 448 content than yellow pea; this aligns with higher concentrations of 449 beta-carotene, which plays an important role in protecting content (Tracewell et al, 2001).…”
supporting
confidence: 88%
“…Around 17 pigments including xanthophylls, chlorophyll a and b related compounds, and (all-E)-b-carotene were identified in pea accessions (Edelenbos, Christensen, & Grevsen, 2001). Lutein and b-carotene have also been identified in FP with green, yellow and orange cotyledons (Holasová, Dostálová, Fiedlerová, & Horáček, 2009). …”
Section: Resultsmentioning
confidence: 99%